Patos Lagoon, Brazil, Suspended Particulate Matter (SPM) data compendium. (24th October 2021) - Távora, Juliana; Leão Fernandes, Elisa Helena; Möller, Osmar Olinto
Abstract: Patos Lagoon is the largest choked coastal lagoon in the world (250 km long, 40 km wide and mean depth of 5 m), with banks formed by sand and predominantly muddy bottom. The circulation is mainly driven by wind and river flow, with a minor contribution of the local microtidal regime. This lagoon is one of the most studied coastal water bodies in Brazil. The Patos Lagoon suspended particulate matter (SPM) data compendium consists of over four decades (1978–2019) of SPM data gathered from multiple research and monitoring projects. Data consist of SPM in situ samplings, remote sensing derived SPM estimates, rating curve approach for SPM estimates and SPM derived from turbidity measurements. Only measurements with a detailed description of the sampling and analysis protocols were used. The present data set offers valuable contributions as it allows the assessment of trends on the data and the short‐ and long‐term spatial and temporal variability of SPM concentrations in an area where permanent monitoring stations are not available. From these records, the SPM concentrations ranged from 0.4 g/m 3 up to 1, 000 g/m 3 . The Patos Lagoon SPM Compendium has been made publicly available at Tavora, Fernandes and Möller (2020). Abstract : In this paper, we report on 41 years of suspended particulate matter (SPM) samples in the largest choked coastal lagoon in the world (250 km long, 40 km wide) – Patos Lagoon, Brazil. The data set consists of 17 data sets which were recovered and filtered for good quality of SPM with temporal coverage from 1978 to 2019. The present data set offers valuable contributions as it allows the assessment of trends on the SPM budget and the short‐ and long‐term spatial and temporal variability of SPM concentrations in an area where permanent monitoring stations are not available.